Analysis of the Corporate Social Responsibility Disclosure on Manufacturing Companies - Putu Kepramareni; Sagung Oka Pradnyawati; Luh Pasek Intan Rahmayani (Jurnal Ekonomi dan Bisnis Jagaditha, 2022)
The line of business cannot be separated from various responsibilities that must be fulfilled. The company is not only responsible to internal parties but also to external parties involving the environment and social (corporate social responsibility). The implementation of CSR can theoretically form a positive image and reputation from the community and shareholders for the company, this is also supported by the existence of CSR disclosures that can be submitted in the company's financial statements. The reality is that even though it is theoretically considered that way, not all companies are willing or able to carry out one of these responsibilities. The purpose of this study is to analyze how CSR disclosure and what can affect the disclosure by using one of the industrial sectors with the largest number in the capital market, namely manufacturing companies. Overall data obtained by literature study, in terms of determining the sample several criteria were used in order to obtain 112 companies and then analyzed using multiple linear regression. The results show that 112 companies used as samples disclose CSR in published financial statements, but this number is not the total number of manufacturing companies that have gone public on the capital market, so there are still many manufacturing companies that do not disclose CSR.